ETIKA KEPOLISIAN SEBAGAI PILAR PENEGAKAN HUKUM KEADILAN - Syahri Syahri; Masfaqihan Masfaqihan; Ali Muzakar (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to analyze police ethics in Indonesia and its influence on public trust. Within the realm of law enforcement, police ethics are vital, especially in addressing persistent social challenges and increasing criminal activity. The research employs a qualitative descriptive analytical methodology, gathering data through in-depth interviews and case studies focused on ethical violations. The findings reveal that a robust ethical framework can significantly boost public confidence in the police, even in the face of ongoing issues such as corruption, human rights abuses, and discrimination. Ethical law enforcement is anticipated to alleviate social inequalities and guarantee equitable treatment for all individuals. Concluding this research, the emphasis is placed on the necessity of establishing a clear code of ethics and providing ongoing training for police officers. Recommendations highlight the importance of implementing stricter accountability mechanisms and fostering constructive dialogue between the police and the community to better understand public expectations and concerns. By enhancing transparency and accountability, it is hoped that the relationship between the police and the community can evolve into a more harmonious one. This research provides valuable insights for fostering public trust in law enforcement agencies and reinforcing their integrity in fulfilling their responsibilities towards justice and public safety.